Prednosti in pasti prostorskega planiranja na regionalni ravni - Šolar, Helena (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
The article states and arguments the reasons for renewed enforcement of spatial planning at regional level through Regional Concepts of Spatial Development. The focus of the article deals with experience gained through preparation procedures of the Regional Concepts of Spatial Development. The conclusion sets out some of the most important pending questions and expected problems which are directly linked to Regional Concepts of Spatial Development and suggests future perspectives in this field of spatial planning.
Keywords: Slovenia; Slovenija; regionalno planiranje; regionalni razvoj; prostorsko planiranje; spatial planning; regije